2002
DOI: 10.1002/pon.591
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of group exercise training (GET) for women with primary breast cancer: feasibility and health benefits

Abstract: Evidence is accumulating for physical activity as an effective, well-tolerated, highly rewarding complementary behavioral intervention for enhancing quality of life (QOL) as well as fitness among individuals with chronic and even terminal illnesses. However, relatively few studies have examined the feasibility and potential health benefits of supervised, structured exercise programs for sedentary women with primary breast cancer. Forty women over the age of 45 with primary breast cancer participated in a cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
148
2
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 28 publications
16
148
2
6
Order By: Relevance
“…The variables that were included in the Pearson Product-Moment correlation model were: ∆ S = Overall muscular strength final assessment -overall strength pre-surgery and ∆ F = Fatigue levels final assessment -fatigue levels pre-surgery. The results of the correlation analysis are presented in table 5. observed (19)(20)(21) . The reason for the contradictory results observed in the present study may be attributed to the small sample size, the muscular strength assessment protocol, and/or duration and intensity of the exercise protocol used in the study.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The variables that were included in the Pearson Product-Moment correlation model were: ∆ S = Overall muscular strength final assessment -overall strength pre-surgery and ∆ F = Fatigue levels final assessment -fatigue levels pre-surgery. The results of the correlation analysis are presented in table 5. observed (19)(20)(21) . The reason for the contradictory results observed in the present study may be attributed to the small sample size, the muscular strength assessment protocol, and/or duration and intensity of the exercise protocol used in the study.…”
Section: Resultsmentioning
confidence: 98%
“…The reason for the contradictory results observed in the present study may be attributed to the small sample size, the muscular strength assessment protocol, and/or duration and intensity of the exercise protocol used in the study. In a study by Kolden et al (20) , forty breast cancer patients underwent an exercise intervention consisting of one hour sessions of warm-up, aerobic, resistance, and cool-down exercises three days a week for sixteen weeks. Kolden et al (20) found significant changes in muscular strength in women who adhered to the exercise program during the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these programs were offered to individuals in group format and these reported improvement in quality of life, physical functioning and fatigue in cancer patients during primary treatment [3][4][5][6][7][8][9][10] and after completion of initial treatment [11][12][13][14]. Recently, interest has been growing in patients' experience with training within groups.…”
Section: Introductionmentioning
confidence: 99%
“…Individualized exercise programs have also been helpful in preserving or improving physical and cardiorespiratory fitness either during or after cancer treatment [9 -15], and home-based exercise programs have demonstrated beneficial effects on fatigue, physical functioning, mood, sleep, and quality of life for these patients [16 -18] . However, prior studies have been limited by focusing on single diagnoses, usually breast or prostate cancer [12][13][14][15], excluding patients undergoing chemotherapy [19], small samples, or reliance on supervised exercise programs [19 -21]. To address this knowledge gap, the primary aim of this study was to test the hypothesis that participants with solid tumors receiving radiation and/or adjuvant chemotherapy who participated in a homebased walking exercise intervention would demonstrate improved sleep quality, better emotional well-being, and lower levels of fatigue when compared to participants who were not offered the intervention.…”
Section: Introductionmentioning
confidence: 99%